ACCURATE DIAGNOSIS OF ACUTE URINARY TRACT INFECTION IN CHILDREN - Aleksandra Vujović; Tanja Kersnik Levart (The Society for Children with Metabolic Disorders, 2023)
Urinary tract infections are one of the most common bacterial infections in children of all ages. They are especially common in infants and small children. Sometimes, they can present as a life-threatening condition. In combination with congenital anomalies of the kidney and urinary tract, complications like arterial hypertension, chronic kidney disease and endstage renal disease can be expected. Accurate diagnosis is, therefore, crucial. Diagnosis is made based on clinical and laboratory signs in combination with significant bacteriuria or positive urine culture of accurately taken urine samples. In this review article, » Accurate diagnosis of acute urinary tract infection in children«, the authors present all essential steps in accurate diagnosis of acute urinary tract infection from clinical picture, laboratory signs, results of imaging, means of accurate urine sampling to means of diagnosing bacteriuria and definition of significant and asymptomatic bacteriuria. A proposed algorithm for clinicians that should be followed when a urinary tract infection is suspected is also presented.